Kaizen in Japan: An Empirical Study - New, S; Adam, A (2003)
This paper reports the study of kaizen as practised in a selection of Japanese companies. After discussing the general understanding of kaizen and proposing a clear definition, the paper describes the methodology of the study, and presents findings from the research, taking Nippon Steel Corporation (NSC) as a base model and comparing this with the data from other companies. The development of kaizen activity in NSC is presented together with a description of the current nature of kaizen, which is compared with other firms in the steel and automotive industries to assess uniformity. The paper concludes that kaizen evolves uniquely within each organisation, following changes to the organisation's business environment. Detailed implementations vary considerably between organisations, but all rely on kaizen to achieve targets as an integral element in the operations management system. This yields insights into kaizen's sustainability, and points to its vulnerability to external economic conditions.